An Overview of Serologic Test Results in Covid-19 Patients: Gambaran Hasil Pemeriksaan Serologi pada Pasien Covid-19 - Kesuma, Suryanata (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 protein and antibody/serology assays can be used for sero-surveillance studies and analyze the epidemiology and virology of SARS-CoV-2. This study aims to review the results of serological tests in Covid-19 patients with the parameters of IgM and IgG antibodies, C-Reactive Protein, procalcitonin, and serum ferritin through literacy studies. This research is descriptive. The study was conducted by collecting and reviewing data on the results of serological examinations in Covid-19 patients contained in articles and journals. After collecting data, 10 journals were obtained that matched the inclusion criteria set by the researcher. The conclusion of this study was that there was an increase in c-reactive protein and procalcitonin levels in Covid-19 patients, serum ferritin levels were also found to tend to increase. IgM antibodies were found to increase earlier than IgG antibodies, but their levels decreased more quickly. An increase in IgG antibodies occurs around the second week after the onset of symptoms.